2008
DOI: 10.1111/j.1574-6968.2008.01304.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution ofArchaeain Japanese patients with periodontitis and humoral immune response to the components

Abstract: There is controversy regarding the existence of archaeal pathogens. Periodontitis is one of the human diseases in which Archaea have been suggested to have roles as pathogens. This study was performed to investigate the distribution of Archaea in Japanese patients with periodontitis and to examine the serum IgG responses to archaeal components. Subgingival plaque samples were collected from 111 periodontal pockets of 49 patients (17 with aggressive periodontitis and 32 with chronic periodontitis), and 30 subgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
77
4
14

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(100 citation statements)
references
References 30 publications
(45 reference statements)
5
77
4
14
Order By: Relevance
“…Total bacterial control indicated that for a C T value of Ͼ35.5, M. oralis detection was not interpretable. Based on these controls, the detection of M. oralis DNA in healthy individuals (C T Յ 35.5) was possible, in contrast to findings of previous studies (12,13,17,18), and a significant correlation was observed between the M. oralis load and periodontitis severity.…”
contrasting
confidence: 53%
See 2 more Smart Citations
“…Total bacterial control indicated that for a C T value of Ͼ35.5, M. oralis detection was not interpretable. Based on these controls, the detection of M. oralis DNA in healthy individuals (C T Յ 35.5) was possible, in contrast to findings of previous studies (12,13,17,18), and a significant correlation was observed between the M. oralis load and periodontitis severity.…”
contrasting
confidence: 53%
“…PCR systems previously used to detect methanogens in the subgingival plaque (6,8,12,13) were not completely specific for M. oralis. Indeed, other methanogens, including Methanobrevibacter smithii (14), Methanosphaera stadtmanae (6), Methanobacterium curvum/Methanobacterium congolense, and Methano-sarcina mazeii (15,16), have been detected in this situation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…periodontal disease. 20 Sixteen studies were selected [8][9][10][11][12][13][14][15]23,[26][27][28][29][30][31] and Methanobrevibacter, Methanosphaera, Methanosarcina, Thermoplasmata and Methanobacterium were considered the five most common genera of methanogenic Archaea present in the subgingival biofilm. In addition, the pooled prevalence of these studies showed that M. oralis was detected in 41% of the periodontitis subjects in comparison with only 6% of the periodontally healthy subjects (p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Furthermore, recent studies have implicated microorganisms other than bacteria with the aetiology of periodontitis, such as certain viruses 6,7 and species from the Archaea domain. [8][9][10][11][12][13][14][15] Archaea are a group of single-cell microorganisms that were classified, based on the sequence of ribosomal RNA genes, as a distinct group of organisms, differing greatly from Bacteria and Eukaryotes 16 in terms of genetic, biochemical, and structural features. 17,18 Several studies have shown that Archaea can be isolated from subgingival samples of periodontitis patients, 10,[12][13][14][15]19,20 infected root canals, 21,22 and in sites with peri-implantitis.…”
Section: Introductionmentioning
confidence: 99%